Using Schmid-Leiman Solution with higher-order constructs in marketing research - Sharma, Piyush; Sivakumaran, Bharadhwaj; Mohan, Geetha (Emerald, 2022)
Purpose: This paper aims to introduce the Schmid–Leiman solution (SLS) as a useful tool to interpret the results of higher-order factor analyses in marketing research irrespective of the type of higher-order factor structure used (formative or reflective).